Water molecule ionization by proton impact experiment and GTO-First Born theory. Issue 15 (January 2020) - Della Picca, R; Cariatore, D; Fiol, J; Fregenal, D; Bernardi, G
Synopsis: In this communication we present calculations and measurements of water ionization by protons at intermediate and high impact energies. The main goal of the present theoretical approach is the development of a method to routinely incorporate sophisticated wavefunctions for small and medium-sized molecules in the determination of ionization cross-sections.